The Potency and Quality of Goat’s Semen for Technological Application of Artificial Insemination - Fitra Aji Pamungkas (Indonesian Center for Animal Research and Development, 2009)
The productivity of local goat is still relatively lower compared to that of other breed for sub-tropic area. Efforts for increasing its productivity through crossbreeding with genotypes goat could be approached by technological application of artificial insemination (AI). In supporting this technology, the viability of semen for both quality and quantity is needed. Evaluation of Indonesian goat semen characterisation shows a potency for frozen semen. The survive ability of sperm in fresh semen is very limited therefore reducing the temperature to -5°C (chilled semen) or -196°C (frozen semen) could be done to maintain its survive ability. Optimalization of frozen semen could be done by diluting in Tris extender with 6% glycerol, equilibrating for 4 hours and cooling for 4 – 5 minutes above surface of LN2 before stored in LN2 (-196°C). Thawing at > 7°C for 30 seconds resulted in the highest percentage of mortility (52.0%) and survivability (65.03%). Chilled semen is the best alternative for artificial insemination (AI) in the field condition where the supply of container and liquid nitrogen are limited. The survivability of chilled semen could be maintained for 8 days and the highest percentage of pregnancy resulted from chilled semen stored up to 24 – 48 hours. Key words : Goat, semen quality, frozen semen, chilled semen, artificial insemination